Sensibility analysis and evaluation of a simulation model to estimate the caloric balance in cattle in the humid tropics - S?nchez, Berenice; Mendoza, G. D.; Plata, F. X.; Vargas, L.; Mart?nez, J. A.; Arcos-Garc?a, J. L. (Cuban Journal of Agricultural Science, 2012)
A sensibility analysis of the model of caloric balance was performed in cattle. The factors related to the radiation (sun radiation exposure hours) were of greater influence on the estimated caloric load. The intake of energy, the liveweight, and the temperature of the humid bulb had lower effect. The rest of the variables had little effect on the outcome of the model. The estimation of the original model resulted in an excessive caloric load (from 9.8 to 16.9 Mcal/d), which was little viable biologically, thus, the model was modified in terms of sun radiation according to the day time. Once modified, the estimations were within the range from 1.3 to 4.8 Mcal/d, which was more likeable from the biological point of view. Key words: caloric stress, environmental effect, management strategies, heat load.